Genetic basis for personalized medicine in asthma - Portelli, Michael A.; Sayers, Ian (Expert Reviews, 2012)
There is heterogeneity in patient responses to current asthma medications. Significant progress has been made identifying genetic polymorphisms that influence the efficacy and potential for adverse effects to asthma drugs, including; β2-adrenergic receptor agonists, corticosteroids and leukotriene modifiers. Pharmacogenetics holds great promise to maximise clinical outcomes and minimize adverse effects. Asthma is heterogeneous with respect to clinical presentation and inflammatory mechanisms underlying the disease, which is likely to contribute to variable results in clinical trials targeting specific inflammatory mediators. Genome-wide association studies have begun to identify genes underlying asthma (e.g., IL1RL1), which represent future therapeutic targets. In this article, we review and update the pharmacogenetics of current asthma therapies and discuss the genetics underlying selected Phase II and future targets.